Penggunaan Media Audiovisual untuk Meningkatkan Motivasi Belajar Al-Qur’an Hadis di MAS Al-Azhar Pamekasan Jawa Timur - Sulasih, Rita; Sofyan, Rizal; Aini, Romi Zatul (EduSpirit : Jurnal Pendidikan Kolaboratif, 2025)
This study aims to analyze the effectiveness of using audiovisual media to enhance students’ motivation in learning Al-Qur’an Hadith at MAS Al-Azhar Pamekasan, East Java. The research employs Classroom Action Research (CAR) using the Kemmis and McTaggart model, consisting of planning, action, observation, and reflection in two cycles. The subjects are 11th-grade students experiencing decreased motivation in Al-Qur’an Hadith learning. Data were collected through observations, interviews, motivation questionnaires, and documentation. The findings indicate that implementing audiovisual media, such as interactive videos, animations, and learning applications, significantly increases students’ motivation. In the first cycle, motivation improved by 25%, while in the second cycle, it increased to 45%. The use of audiovisual media makes learning more engaging, easier to understand, and interactive, thereby enhancing students’ engagement and interest in Al-Qur’an Hadith subjects. This study concludes that using audiovisual media is an effective teaching strategy to boost students’ motivation at the Madrasah Aliyah level.